Allopregnanolone and mood in the peripartum: a longitudinal assessment in healthy women - Grötsch, Maria Katharina; Ehlert, Ulrike (Frontiers in Behavioral Neuroscience, 2024)
Background: Allopregnanolone (ALLO), a neuroactive steroid hormone derived from progesterone, can modulate mood via the GABA-A receptor. Peripartum mood can be influenced by psychosocial factors, previous mental illness, and hormonal changes. Studies suggest a U-shaped effect of ALLO on mood, with some women being more sensitive to hormonal changes than others. However, research in the peripartum is inconclusive. Methods: This study explored the link between salivary ALLO and mood during the peripartum. Over 12 weeks, N = 61 women completed the Edinburgh Postnatal Depression Scale and the State Anxiety subscale from the State-Trait Anxiety Inventory and provided saliva samples. Salivary ALLO was analyzed using an enzyme-linked immunosorbent assay, validated for saliva samples. Group-based trajectory modeling was performed to identify trajectories of ALLO courses. Multinomial logistic regression models were employed to identify risk factors associated with these trajectories. Results: ALLO levels increased during pregnancy and dropped two weeks before delivery. Three different trajectory groups of ALLO courses emerged (high decreasing, low moderate, low reduced). Trajectory groups were associated with distinct psychological risk factors, including previous mental illness, adverse childhood experiences, sleep problems, premenstrual symptoms, and resilience. The peripartum ALLO course showed a negative linear association with anxiety symptoms and a U-shaped association with depressive symptoms. Discussion: The consideration of individual ALLO courses can predict the risk for peripartum mood symptoms, particularly among women with preexisting risk factors. While the majority of women remain healthy during the peripartum transition, analyzing ALLO subgroups helps to provide a better understanding of the relation-ship between ALLO and peripartum mood.